2020
DOI: 10.3389/fped.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 15 Imprinting Disorders: Genetic Laboratory Methodology and Approaches

Abstract: Chromosome 15 imprinting disorders include Prader-Willi (PWS) and Angelman (AS) syndromes, which are caused by absent expression from the paternal and maternal alleles in the chromosome 15q11. 2-q13 region, respectively. In addition, chromosome 15q duplication caused by the presence of at least one additional maternally derived copy of the 15q11.2-q13 region can lead to seizures, cognitive and behavioral problems. We focus on PWS and AS in the report, and expand the discussion of clinical care and description … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…AS is caused by the loss or mutation of regional imprinting and maternal genes especially influences on the UBE3A gene. UBE3A is the only gene in 15q11‐q13 that shows maternal allele preference (Butler & Duis, 2020; Gu et al, 2019). Microdeletion of 15q11 causes 70% to 90% of cases, UPD causes 3% to 7% of cases, and single‐gene defects cause only 2% to 4% of cases (Neubert et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…AS is caused by the loss or mutation of regional imprinting and maternal genes especially influences on the UBE3A gene. UBE3A is the only gene in 15q11‐q13 that shows maternal allele preference (Butler & Duis, 2020; Gu et al, 2019). Microdeletion of 15q11 causes 70% to 90% of cases, UPD causes 3% to 7% of cases, and single‐gene defects cause only 2% to 4% of cases (Neubert et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These typical deletions are seen in both PWS and AS. Also, atypical 15q11-q13 deletions that are larger or smaller than the typical deletions are seen in about 7% of patients with PWS or AS as a cause ( Beygo et al, 2019 ; Butler et al, 2019a ; Butler and Duis, 2020 ) and would be identified with this streamlined approach for molecular diagnostics. The results were compared with the MLPA copy number assessment for orthogonal confirmation.…”
Section: Methodsmentioning
confidence: 99%
“…not from non-deletion maternal heterodisomy 15 status (Butler et al, 2019a;Butler and Duis, 2020). The streamlined molecular diagnostic approach we describe will identify microdeletions as well as point mutations in the imprinting center and therefore should eliminate the need for additional testing using genotyped chromosome 15 markers with parental DNA.…”
Section: Head-to-head Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…PWS is recognized as the first example of errors in genomic imprinting and accounts for about 1 in 15,000 live births with more than 400,000 individuals worldwide. [1][2][3][4][5][6] Background Certain abnormal neurodevelopmental behavioral features in PWS specifically skin picking are more common than in other syndromes with intellectual disability. Skin picking is found in 81% of individuals with PWS at an average age of 18 years with 40% of all self-injurious behavior occurring on the legs (41%), particularly the front, 42% on the head including…”
Section: Introductionmentioning
confidence: 99%